FORMATION OF CHORAL CONDUCTING SKILLS IN THE PROFESSIONAL TRAINING OF THE FUTURE MUSIC TEACHER IN HIGHER EDUCATIONAL INSTITUTIONS - Bondarenko, A.V. (Pedagogy of Higher and Secondary Education, 2009)
In article the problem of formation of skills of choral conducting in vocational training the future teacher of music is examined.